PENGETAHUAN DAN SIKAP TENTANG TANDA BAHAYA KEHAMILAN BERHUBUNGAN DENGAN PEMANFAATAN BUKU KIA - Dewie, Artika (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2021)
Background : The Maternal and Child Health (MCH) Handbook contains complete information, including early detection or danger signs of maternal health problems from pregnancy to childbirth to increase knowledge of mothers and their families. The attitude of pregnant women about signs of pregnancy is important in changing the behavior of pregnant women in dealing with signs of pregnancy. Objective : To determine the relationship between knowledge and attitudes of pregnant women about the danger signs of pregnancy with the use of the MCH Handbook. Method : Using a cross-sectional design. The population used was trimester III pregnant women who had MCH books and were visiting to carry out pregnancy checks at Puskesmas Kota Palu (11 Puskesmas) during the research period in 2019. Using the cluster sampling method with a total of 110 respondents. Primary data were collected through ODK Collect, then analyzed univariate and bivariate. Results : There is a relationship between knowledge about the danger signs of pregnancy and the use of the MCH Handbook (p-value = 0.003). There is a relationship between the attitudes of pregnant women about danger signs and the use of the MCH Handbook (p-value = 0.008). OR = 3,235 indicates that mothers with positive attitudes are 3,235 times more likely to use the MCH handbook than mothers who are negative. Conclusion : There is a relationship between knowledge and attitudes about the danger signs of pregnancy and the use of the MCH Handbook. Keywords: Knowledge, Attitudes, danger sign of pregnancy, MCH Handbook.